Mental health articulation and solidary economy: report of a social inclusion project - Pedroza, Ariadne Pereira; Oliveira, Francisca Bezerra de; Fortunato, Maria Lucinete; Soares, Perla Figueredo Carreiro (Rev Rene, 2012)
The Psychiatric Reform has as one of the main devices the potentialization of work as a social inclusion instrument. This study has sought to describe the experience lived and the activities developed of the Training Extension Project of Users of the Center of Psychosocial Attention of Cajazeiras – PB (CAPS) for the Production of Handicraft Artifacts. It is a report of experience whose developed activities were described thoroughly. It has been perceived that the difficulties found were overcome, favoring like this, in a shy and incipient way, the income production and the improvement in the life quality of each one. It becomes urgent the necessity of the implementation of municipal public policies which promotes the articulation between mental health and solidary economy, contributing to reflections about health care to people in psychic suffering.